Simulation of indicative control system by local innovation projects - Savchuk, R. V. (Science and Transport Progress, 2011)
The method of determination of basic parameters of forming of models of cutting of costs, related to the property risks is offered. For forming of models the exponential distribution is used for description of distributing of size of really nascent losses during realization of property risks.